Functionalized methoxy quinoline derivatives: Experimental and in silico evaluation as new antiepileptic, anti-Alzheimer, antibacterial and antifungal drug candidates - Bilge Çi̇ftci̇; Salih Ökten; Ümit Muhammet Koçyi̇ği̇t; Vildan Enisoğlu Atalay; Mehmet Ataş; Osman Çakmak (Elsevier, 2024)
The objective of this study was to assess the inhibitory effects of newly synthesized quinoline derivatives on human carbonic anhydrase I and II (hCA I and II), as well as acetylcholinesterase (AChE) enzymes, alongside their impact on various microorganisms. The synthesized compounds were assessed using IC50, Ki and MIC values via Ellman and Esterease Method and Microdilution assay. Most compounds exhibited strong inhibitory effects on human carbonic anhydrase I and II (hCA I and II) and acetylcholinesterase (AChE), notably compounds 9, 12, and 17 for hCA I, and 9, 12, 16 and 17 for hCA II, alongside robust AChE inhibition by compounds 8 and 13. Antimicrobial tests highlighted compounds 13 and 15 as promising inhibitors against pathogens, particularly effective across various strains. Molecular docking supported these findings, indicating potent binding abilities, notably by compounds 16 and 17 across specific protein structures (2COP, 5E2M, and 6KM3). The discussion emphasized the impact of substituents, particularly methoxy groups at specific positions, on enzyme inhibition, revealing how structural modifications affected enzyme inhibitory properties. The comprehensive analysis bridged experimental and computational findings, uncovering essential structure-activity relationships in quinoline derivatives and identifying potential candidates for further studies in enzyme inhibition and antimicrobial research.